Non-clinical safety profile and pharmacodynamics of two formulations of the anti-sepsis drug candidate Rejuveinix (RJX) - Uckun, Fatih M.; Orhan, Cemal; Powell, Joy; Sahin, Emre; Ozercan, Ibrahim H.; Volk, Michael; Şahin, Kazım (Elsevier France-Editions Scientifiques Medicales Elsevier, 2021)
Here, we demonstrate that the two distinct formulations of our anti-sepsis drug candidate Rejuveinix (RJX), have a very favorable safety profile in Wistar Albino rats at dose levels comparable to the projected clinical dose levels. 14-day treatment with RJX-P (RJX PPP.18.1051) or RJX-B (RJX-B200702-CLN) similarly elevated the day 15 tissue levels of the antioxidant enzyme superoxide dismutase (SOD) as well as ascorbic acid in both the lungs and liver in a dose-dependent fashion. The activity of SOD and ascorbic acid levels were significantly higher in tissues of RJX-P or RJX-B treated rats than vehicle-treated control rats (p 0.0001). There was no statistically significant difference between tissue SOD activity or ascorbic acid levels of rats treated with RJX-P vs. rats treated with RJX-B (p 0.05). The observed elevations of the SOD and ascorbic acid levels were transient and were no longer detectable on day 28 following a 14-day recovery period. These results demonstrate that RJX-P and RJX-B are bioequivalent relative to their pharmacodynamic effects on tissue SOD and ascorbic acid levels. Furthermore, both formulations showed profound protective activity in a mouse model of sepsis. In agreement with the PD evaluations in rats and their proposed mechanism of action, both RJX-P and RJX-B exhibited near-identical potent and dose-dependent anti-oxidant and anti-inflammatory activity in the LPS-GalN model of ARDS and multi-organ failure in mice.
Keywords: Cancer; Sepsis; Pneumonia; ARDS; Acute lung injury (ALI); Multi-organ dysfunction (MODS); Cytokine release syndrome (CRS); COVID-19